2019
DOI: 10.1111/mec.15177
|View full text |Cite
|
Sign up to set email alerts
|

Land use is a determinant of plant pathogen alpha‐ but not beta‐diversity

Abstract: Little is known about the diversity patterns of plant pathogens and how they change with land use at a broad scale. We employed DNA metabarcoding to describe the diversity and composition of putative plant pathogen communities in three substrates (soil, roots, and leaves) across five major land uses at a national scale. Almost all plant pathogen communities (fungi, oomycetes, and bacteria) showed strong responses to land use and substrate type. Land use category could explain up to 24% of the variance in compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 60 publications
0
55
1
Order By: Relevance
“…Presumably, invasion by B . alba tends to alter the community structure of bacteria rather than diversity, thereby facilitating further invasion processes [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, invasion by B . alba tends to alter the community structure of bacteria rather than diversity, thereby facilitating further invasion processes [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The change in land cover from native cover to pasture was associated with a shift in dominance of Alphaproteobacteria and Actinobacteria taxa towards more Gammaproteobacteria, Betaproteobacteria, and Bacilli. Makiola et al (2019) showed that the alpha-diversity of plant pathogens (fungal, oomycete and bacterial) was much higher in modified land-uses than natural forests. Furthermore, changes in microbial communities that occur within a landuse type can impact adjoining ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…DNA metabarcoding generates massive amounts of data on taxonomic units (e.g., operational taxonomic units, OTUs, or exact sequence variants, ESVs; Callahan et al, 2017) rapidly, and these can be linked increasingly to functional attributes (Douglas et al, 2018;Makiola et al, 2019). DNA metabarcoding is highly complementary to whole metagenomic and metatranscriptomic sequencing (Knight et al, 2018), existing sources of ecological information (Cordier et al, 2018;Derocles et al, 2018) and classical biomonitoring approaches (Deiner et al, 2017); in all cases, adding genomic and/or ecological information to the rich taxonomic lists afforded by DNA metabarcoding would allow deeper exploration of ecological or biodiversity patterns.…”
Section: Introductionmentioning
confidence: 99%